2015
DOI: 10.1007/978-3-662-45950-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-responsive Wormlike Micelles

Abstract: This chapter summarizes findings on the simplest trigger applied to wormlike micellar: temperature. Thermo-thinning systems are not discussed since a viscosity decrease with temperature is a rather general characteristic of most systems. Instead, the unique thermo-viscosifying behaviour displayed by some WLMs and the possibility of imparting a pseudo "sol/gel" transition in specific systems are extensively addressed. These two types of systems show a transition from either a low-viscosity fluid or a viscoelast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…It has been reported that surfactant systems, especially the anionic ones, generally manifest a parabolic viscosity–temperature behavior . This behavior can be utilized to modulate the viscosity profiles of home care products by a careful formulation design to achieve an ideal viscosity in which case the system goes through a stretched parabolic curve, resulting in an accepting viscosity profile in the low-temperature range, and the system would not go through a monotonic increase when the temperature decreases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that surfactant systems, especially the anionic ones, generally manifest a parabolic viscosity–temperature behavior . This behavior can be utilized to modulate the viscosity profiles of home care products by a careful formulation design to achieve an ideal viscosity in which case the system goes through a stretched parabolic curve, resulting in an accepting viscosity profile in the low-temperature range, and the system would not go through a monotonic increase when the temperature decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Although parabola-type formulas have been reported in some cases, gemini or cationic surfactants have to be used in these formulas, and the vertex of the parabola is located in the high-temperature region, higher than room temperature. , In the meantime, most of the rheological studies have focused on dilute system solution, and only a few reports have studied the concentrated surfactant solution, which is close to the real applications. It has been reported that, in a concentrated solution, a giant micelle including wormlike micelle will be formed, which is an important hotspot in surfactant studies due to its unique polymer-like behavior. , In dilute surfactant systems, the shape transition of micelles can be studied by static and dynamic light scattering, while it is not feasible in a concentrated solution. Thus, the giant micelle for the latter has been studied by rheology, NMR, SANS, and visually FF-TEM or cryo-TEM. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation